2011
DOI: 10.1186/1477-7827-9-161
|View full text |Cite
|
Sign up to set email alerts
|

Circulating LH/hCG receptor (LHCGR) may identify pre-treatment IVF patients at risk of OHSS and poor implantation

Abstract: BackgroundSuccessful pregnancy via in vitro fertilization (IVF) depends on the recovery of an adequate number of healthy oocytes and on blastocyst implantation following uterine transfer. Two hormones, LH and hCG, utilize a common LH/hCG receptor (LHCGR), variations in which have profound implications in human reproduction. Soluble LHCGR (sLHCGR) is released from experimental cell lines and placental explants and it can be detected in the follicular fluid and serum.MethodsTo evaluate the impact of circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…The protein identified in the current study of around 75 kDa in serum from men with TGCTs may be representing the full-length receptor, while the lower molecular weight band (50 kDa) may represent a truncated or cleaved receptor protein. This suggestion is supported by showing similar band sizes in gonadal tissues and is in accordance with previous studies investigating LHCGR in serum [ 10 , 35 , 36 ]. We hypothesized that the circulating LHCGR or its fragment could have diagnostic potential in patients with TGCT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The protein identified in the current study of around 75 kDa in serum from men with TGCTs may be representing the full-length receptor, while the lower molecular weight band (50 kDa) may represent a truncated or cleaved receptor protein. This suggestion is supported by showing similar band sizes in gonadal tissues and is in accordance with previous studies investigating LHCGR in serum [ 10 , 35 , 36 ]. We hypothesized that the circulating LHCGR or its fragment could have diagnostic potential in patients with TGCT.…”
Section: Discussionsupporting
confidence: 92%
“…Later, it was identified in the medium of ligand-induced rat and mouse Leydig cells [ 34 ] or human cells transfected with cloned LHCGR [ 18 , 35 ]. In humans, LHCGR has been found in serum and follicular fluid of women [ 10 ] and by proteomics in serum from men and women [ 36 ] but could it also be released from seminoma cells and be measured in serum? We have recently shown that different LHCGR fragments are released into serum of healthy men [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratories had shown that the expression of soluble LHCGR (sLHCGR, N-terminal 336 residues of the extracellular domain) as a thioredoxin fusion protein in E . coli carrying mutations in both thioredoxin reductase ( TrxB ) and glutathione reductase ( gor ) genes [14], had a similar specificity and affinity for hCG as the intact native LHCGR [15]. Therefore, this protocol was followed in order to produce the sLHCGR standard calibrator for ELISA assays.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, hCG has been shown to specifically upregulate MMP-2 and MMP-9 [ 11 , 12 ] and several studies have shown post-transcriptional regulation of LHCGR [ 13 , 14 ]. Soluble LHCGR (sLHCGR) has been measured by an ELISA platform in both serum and follicular fluid from women [ 15 , 16 ]. The specificity of the antibodies used in the ELISA assay were validated by expressing different LHCGR fragments in CHO cells for epitope mapping and by examining expression in the human placenta [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%